1970
DOI: 10.4314/ejhs.v28i6.15
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Prescribing Decisions of Physicians: A Review

Abstract: BACKGROUND: The pharmaceutical bill is increasing at an alarming rate. The physician practice variation has a pronounced effect on healthcare spending. A number of factors can influence the prescribing behavior of physicians. The aim of this review was to identify the factors affecting the prescribing decision of physicians.METHODS: Electronic databases including Scopus, PubMed/MEDLINE CENTRAL, Cochrane Libraries and Google scholar were searched systematically for literatures on factors influencing prescribing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 64 publications
5
59
0
1
Order By: Relevance
“…Doctors can receive information through a number of sources, such as published articles in medical journals, meetings, conferences, the internet and social media, and most importantly through clinical practice guidelines [ 19 , 20 , 21 , 22 , 23 ]. Various factors can affect the choice of physicians regarding used sources of information such as age, past training, and specialty [ 24 ] in addition to physicians’ familiarity and previous expertise with information systems and sources [ 22 ]. Moreover, convenience of access and the availability and credibility of data supplied by sources can play major roles in the choice of preferred information sources among doctors [ 19 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Doctors can receive information through a number of sources, such as published articles in medical journals, meetings, conferences, the internet and social media, and most importantly through clinical practice guidelines [ 19 , 20 , 21 , 22 , 23 ]. Various factors can affect the choice of physicians regarding used sources of information such as age, past training, and specialty [ 24 ] in addition to physicians’ familiarity and previous expertise with information systems and sources [ 22 ]. Moreover, convenience of access and the availability and credibility of data supplied by sources can play major roles in the choice of preferred information sources among doctors [ 19 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of suitable and reliable practice guidelines could decrease the harmful impact of certain factors and endorse rational prescribing. [28] Our study was conducted in only one private hospital, which limited the generalisability of the findings. However, in the private sector in SA, doctors often admit and manage patients at more than one hospital; therefore, our findings are likely to reflect the practices at other hospitals in the private sector, particularly in Durban.…”
Section: Researchmentioning
confidence: 94%
“…These included physicians' personal attributes, cost of the medicine and marketing and promotion strategies of the pharmaceutical industry. [28] These factors showed that…”
Section: Researchmentioning
confidence: 99%
“…Heald et al noted an association between testosterone prescribing and GP practice rating, and patient preference is indeed an important factor influencing prescribing behaviour. 10 However, much more detailed work is needed to determine whether 'better rated' practices are over-prescribing testosterone, or as Heald et al appear to assume, are the only ones that are prescribing enough testosterone. Indeed, a UK-based study reported a 90% increase in testosterone prescriptions in men between 2001 and 2010 albeit the number of men with unequivocal biochemical hypogonadism (testosterone less than 6.0 mol/L) remained unchanged.…”
mentioning
confidence: 99%